PORTFOLIO AS ONE OF THE LEARNING EVALUATIONS IN THE CCU (CROSS CULTURAL UNDERSTANDING)SUBJECT - Titi Rokhayati (CLLiENT (Culture, Literature, Linguistics, and English Teaching), 2020)
There were two evaluations, measurement and assessment. The instruments of the evaluation must be valid and reliable. In the teaching and learning process, it had three aspects, input, process and outputs. The outputs had close relationship with evaluation. One of the kinds of evaluation was using portfolio in which the students’ work was being considered thoroughly. By using portfolio, a teacher was able to evaluate the students in detail. This research was descriptive qualitative in which it had 5 students as the subject and several students’ work as the object of the research. The result proved that portfolio can be applied to CCU (Cross Cultural Understanding) subject by considering some steps; 1) compile the students’ work, 2) make a rubric for each student, 3) evaluate the process and the results of students’ work. It was also found that portfolio could be an alternative way to evaluate CCU subject.